Quantitative interocular suppression in children with intermittent exotropia - Chen, Hui; Jiang, Xiaohui; Liu, Weijie; Zhou, Jiawei; Chen, Jie; Sun, Qianqian; Liang, Lin; Lou, Jiangtao; Yu, Xinping; Qu, Jia (Frontiers in Neuroscience, 2023)
Purpose We have demonstrated that the depth of unbalanced interocular suppression can be quantified by balancing the interocular luminance differences required when both eyes are viewing simultaneously. In this study, we aimed to investigate the applicability of this method in children with intermittent exotropia (IXT), offering a quantitative assessment of interocular suppression in individuals with binocular imbalance. Additionally, we evaluated its association with the clinical characteristics of IXT. Methods Interocular suppression in IXT was quantitatively measured using a polarizer and neutral-density (ND) filters. The density of the ND filter was adjusted incrementally from 0.3ND to 3ND, with a step size of 0.3ND (a total of 10 levels). Our prospective study involved 46 patients with IXT (mean age: 10.12 ± 4.89 years; mean ± SD) and 24 normal observers (mean age: 7.88 ± 1.83 years). Results The suppression test exhibited good test–retest reliability, supported by statistical analysis. We observed more pronounced interocular suppression in individuals with IXT compared to controls. Notably, the magnitude of suppression during distant and near viewing significantly differed in IXT (1.55 ± 0.93 vs. 0.57 ± 0.64; Z = 4.764, p < 0.001). Furthermore, we identified a positive correlation between interocular suppression and data obtained from the Worth-4-Dot test. Additionally, interocular suppression showed a significant association with distance control scores. Conclusion Our novel test offers a convenient and reliable means to quantify interocular suppression in patients with IXT. The quantitative assessment of interocular suppression provides a sensitive tool to evaluate the clinical characteristics of IXT.